Pengaruh Variasi Masa Pengobatan Obat Anti Tuberkulosis (OAT) terhadap Billirubin dalam Urine Penderita Tuberkulosis Metode Carik Celup - Novitasari, Riska; Urip, Urip; Tatontos, Erlin Yustin; Aprianti, Aurira Thrisna Dwi (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Treatment of Tuberculosis using Anti Tuberculosis Drugs (OAT) has a hepatotoxic effect that can cause liver function disorders, one of which is bilirubin. Examination of bilirubin can use blood and urine. Qualitative and semi-quantitative examination of bilirubin in urine by diazo reaction using the dipstick or dipstick method is widely used because it is fast, more practical, and more sensitive. The purpose of this study was to determine the effect of variations in the treatment period of Anti Tuberculosis Drugs (OAT) on bilirubin in the urine of tuberculosis patients. This research is an analytical observational research. The sample in this study amounted to 20 people in the initial and follow-up treatment periods. Urine samples in patients with tuberculosis were examined for urine bilirubin levels using the dipstick method. The results showed that the level of bilirubin in the urine qualitatively in the early stages of treatment had a positive value, namely 5 out of 9 tuberculosis patients (56%) with a positive level of 1 (+1) semi-quantitatively. The level of bilirubin in the urine qualitatively in the advanced stage of treatment has a positive value, namely 1 out of 11 tuberculosis patients (9%) with a positive level of 1 (+1) semi-quantitatively. The results of the Chi-Square bilirubin test in urine qualitatively and semi-quantitatively showed the value of p = 0.024 < = 0.05. The conclusion is that variations in the treatment period of Anti Tuberculosis Drugs (OAT) have an effect on bilirubin in the urine of tuberculosis patients.